Design and Evaluation of Transdermal Patches of Labetalol Hydrochloride - Kumbhar, Ravindra B. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Î²-blockers like labetalol hydrochloride (LHCl) are potent and highly effective antihypertensive agents. The main drawback associated with Î²-blockers is extensive first-pass metabolism, variable bioavailability requiring frequent dose administration. This makes them an ideal candidate for transdermal therapeutic systems. Î²-blockers formulated as transdermal therapeutic system should enhance the bioavailability as well as improve patient compliance. Constant innovations and improvement in this field have potential that largeâ€scale commercialization of transdermal dosage forms can be done. Aim: The aim of the present work was to develop and evaluate matrix type transdermal patches containing new polymeric combination to enhance the bioavailability as well as improve patient compliance. Materials and Methods: In present work development and evaluation of matrix-type transdermal patches containing a new polymeric combination of HPMC, carbopol934, ethyl cellulose, propylene glycol, polyethylene glycol, and isopropyl myristate for labetalol (LHCl) HCl (LBHCl). Film casting technique has been used in preparing patches. The patches were characterized for physical, in vitro release studies and ex vivo permeation studies using human cadaver skin. Result: F6 was found to be better than the other formulations and hence selected as the optimized formulation on the basis of results of evaluating parameters such as thickness, flatness, folding endurance, tensile strength, moisture content, moisture uptake, and drug content, formulation. The optimized patch was assessed for its pharmacokinetic, pharmacodynamic, skin irritation test and stability studies. Conclusion: Successful development of sustained release matrix type of transdermal patches which can show greater patient compliance in treating hypertension has been done.